PENGARUH KARAKTERISTIK PEKERJAAN DAN KARAKTERISTIK INDIVIDU TERHADAP KEPUASAN KERJA PEGAWAI DINAS PENGELOLAAN PASAR KOTA BANJARMASIN - Mailiana - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, The purpose of this research is to analysis the influence of job characteristics and individual characteristics to job satisfaction of employees at the department of market management Banjarmasin . Data was collected by documentation method, interview method dan questionnare method. Data was analyzed by using multiple regression method. The result of this research is job charcteristics and individual characteristics has significant and positivly influence to job satisfaction. Beside that, this research is also shown that job characteristics has greater influence to job satisfaction individual characteristics than individual characteristics.